2018
DOI: 10.1063/1.5022247
|View full text |Cite
|
Sign up to set email alerts
|

Structure and optical properties of 2D layered MoS2 crystals implemented with novel friction induced crystal growth

Abstract: We used X-ray diffraction, and Raman and photoluminescence (PL) spectroscopies to examine the structure and optical properties of molybdenum disulfide (MoS2) crystals grown by friction at the interface between two materials. MoS2 is produced chemically from molybdenum dithiocarbamates (MoDTC) in synthetic oil under sliding friction conditions. The X-ray diffraction (XRD) patterns indicate that the structure of the MoS2 is layered with the c-axis perpendicular to the surface. The MoS2 layer was formed on stainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…[5] Among these compounds, MoTe 2 exhibits polymorphic phase transitions within hexagonal (2H) and monoclinic (1T′) or orthorhombic (T d ) crystal structures; switching between these phases can also be realized by the application of external stimuli such as temperature, electric-field or pressure. [3,[6][7][8][9][10][11] As a result, MoTe 2 has been extensively studied as a switching layer in nextgeneration non-volatile memories (NVMs), such as resistive random access memory (ReRAM) and phase-change random access memory (PCRAM), due to the large changes in electrical properties ranging from metallic to semiconducting accessable by switching between phases. Zhang et al reported an electric-field-induced structural transition from a 2H semiconducting to a distorted transient [11,15,[29][30][31] the T c and T m values of NbTe 4 were defined by the onset temperature of crystallization and melting peaks in this study; B) XRD curves of NbTe 4 thin films annealed at various temperatures; C) cross-sectional TEM image of 350 °C annealed NbTe 4 thin film; D) zoomed in image of the white-box area in (C); E) the FFT pattern taken from the area of (D).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] Among these compounds, MoTe 2 exhibits polymorphic phase transitions within hexagonal (2H) and monoclinic (1T′) or orthorhombic (T d ) crystal structures; switching between these phases can also be realized by the application of external stimuli such as temperature, electric-field or pressure. [3,[6][7][8][9][10][11] As a result, MoTe 2 has been extensively studied as a switching layer in nextgeneration non-volatile memories (NVMs), such as resistive random access memory (ReRAM) and phase-change random access memory (PCRAM), due to the large changes in electrical properties ranging from metallic to semiconducting accessable by switching between phases. Zhang et al reported an electric-field-induced structural transition from a 2H semiconducting to a distorted transient [11,15,[29][30][31] the T c and T m values of NbTe 4 were defined by the onset temperature of crystallization and melting peaks in this study; B) XRD curves of NbTe 4 thin films annealed at various temperatures; C) cross-sectional TEM image of 350 °C annealed NbTe 4 thin film; D) zoomed in image of the white-box area in (C); E) the FFT pattern taken from the area of (D).…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] Among these compounds, MoTe 2 exhibits polymorphic phase transitions within hexagonal (2H) and monoclinic (1T′) or orthorhombic ( T d ) crystal structures; switching between these phases can also be realized by the application of external stimuli such as temperature, electric‐field or pressure. [ 3,6–11 ] As a result, MoTe 2 has been extensively studied as a switching layer in next‐generation non‐volatile memories (NVMs), such as resistive random access memory (ReRAM) and phase‐change random access memory (PCRAM), due to the large changes in electrical properties ranging from metallic to semiconducting accessable by switching between phases. Zhang et al.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, MoDTC reduces friction by forming a MoS 2 tribofilm on the contact area, [7][8][9][10] whereas ZDDP prevents wear by forming an amorphous tribofilm with multilayered structures. 5,6,11 Thus, recent studies have focused on the influence of metallic and nonmetallic substrates in the tribochemical reactions of MoDTC [12][13][14] and ZDDP. [15][16][17] Chlorine-containing EP additives are commonly used in the cold-working processes of steel because of their cost effectiveness and high lubricity along with high corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, MoDTC reduces friction by forming a MoS 2 tribofilm on the contact area, 7–10 whereas ZDDP prevents wear by forming an amorphous tribofilm with multilayered structures 5,6,11 . Thus, recent studies have focused on the influence of metallic and nonmetallic substrates in the tribochemical reactions of MoDTC 12–14 and ZDDP 15–17 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation